Providing optimal care in the neonatal care units in India: How Covid-19 exacerbated existing barriers. - Lisa Messersmith; Cherryl Kolhe; Alyana Ladha; Prabir Das; Sowmya R Rao; Marym Mohammady; Emily Conant; Rejesh Bose; Nithya Ramanathan; Archana Patel; Patricia L Hibberd (Public Library of Science (PLoS), 2024)
Nearly one quarter (600,000) of all neonatal deaths worldwide per year occur in India. To reduce neonatal mortality, the Indian Ministry of Health and Family Welfare established neonatal care units, including neonatal intensive care units and specialized neonatal care units to provide immediate care at birth, resuscitation for asphyxiation, postnatal care, follow up for high-risk newborns, immunization, and referral for additional or complex healthcare services. Despite these efforts, neonatal mortality remains high, and measures taken to reduce mortality have been severely challenged by multiple problems caused by the Covid-19 pandemic. In this qualitative study, we conducted seven focus group discussions with newborn care unit nurses and pediatric residents and 35 key informant interviews with pediatricians, residents, nurses, annual equipment maintenance contractors, equipment manufacturers, and Ministry personnel in the Vidarbha region of Maharashtra between December 2019 and November 2020. The goal of the study was to understand barriers and facilitators to providing optimal care to neonates, including the challenges imposed by the Covid-19 pandemic. Covid-19 exacerbated existing barriers to providing optimal care to neonates in these newborn care units. As a result of Covid-19, we found the units were even more short-staffed than usual, with trained pediatric nurses and essential equipment diverted from newborn care to attend to patients with Covid-19. Regular training of neonatal nursing staff was also disrupted due to Covid-19, leaving many staff without the skills to provide optimate care to neonates. Infection control was also exacerbated by Covid-19. This study highlights the barriers to providing optimal care for neonates were made even more challenging during Covid-19 because of the diversion of critically important neonatal equipment and staff trained to use that equipment to Covid-19 wards. The barriers at the individual, facility, and systems levels will remain challenging as the Covid-19 pandemic continues.